2016
DOI: 10.1104/pp.16.00325
|View full text |Cite|
|
Sign up to set email alerts
|

Albino Leaf 1 that Encodes the Sole Octotricopeptide Repeat Protein Is Responsible for Chloroplast Development in Rice

Abstract: Chloroplast, the photosynthetic organelle in plants, plays a crucial role in plant development and growth through manipulating the capacity of photosynthesis. However, the regulatory mechanism of chloroplast development still remains elusive. Here, we characterized a mutant with defective chloroplasts in rice (Oryza sativa), termed albino leaf1 (al1), which exhibits a distinct albino phenotype in leaves, eventually leading to al1 seedling lethality. Electronic microscopy observation demonstrated that the numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 43 publications
3
23
1
Order By: Relevance
“…Similarly, the significantly reduced transcripts of rbcL , an indicator for the accumulation of polysomes (Barkan 1993), chloroplast 16SrRNA, 23SrRNA and rps7, rps14, rps20 in the tcd10 mutants indicated that the tcd10 mutation affects the assembly and accumulation of plastid ribosomes, resulting in disruption of plastid translation. Similarly, the blockage of the chloroplast 16SrRNA maturation in Arabidopsis rap mutant (Kleinknecht et al 2014) and rice al1 mutant (Zhang et al 2016) leads to abnormal chloroplasts. Thus, TCD10 participates in not only the plastid translation, but also the assembly and the accumulation of plastid ribosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the significantly reduced transcripts of rbcL , an indicator for the accumulation of polysomes (Barkan 1993), chloroplast 16SrRNA, 23SrRNA and rps7, rps14, rps20 in the tcd10 mutants indicated that the tcd10 mutation affects the assembly and accumulation of plastid ribosomes, resulting in disruption of plastid translation. Similarly, the blockage of the chloroplast 16SrRNA maturation in Arabidopsis rap mutant (Kleinknecht et al 2014) and rice al1 mutant (Zhang et al 2016) leads to abnormal chloroplasts. Thus, TCD10 participates in not only the plastid translation, but also the assembly and the accumulation of plastid ribosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Deficient chloroplast development is always associated with abnormal expression of plastid genes ( Wang et al , 2016 a , 2016 b , Zhang et al , 2016 ). To analyze the effect of the wtg1 mutation on gene expression, we determined the transcription profiles of wild-type, wtg1 , and complemented seedlings using RNA-seq ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Shot gun proteomic analysis of al1 mutant indicated that AL1 controls chloroplast development through regulation of important chloroplast associated proteins such as subunits of different light reaction complexes including PSI, PSII, cytochrome b 6 /f, photosynthetic electron transport and F-type ATPase. Moreover, homeostasis of ribosomal proteins appeared to be important for chloroplast development [59]. Alteration of ribosomal proteins followed also chromoplast differentiation during orange fruit maturation as found by iTRAQ-based proteomic analysis.…”
Section: Using Plastid Ultrastructure Observations In Proteomicsmentioning
confidence: 95%